AIR FLOW VISUALIZATION AROUND THE FLIGHT FLIGHT WINGS - Yosaphat Sumardi (Jurnal Penelitian Saintek, 2003)
This research is performed with objectives: (I) to show the patterns of velocity field  contour of airflow around the wings of subsonic plane, (2) to show factors  that influence these patterns,  and (3)  to explain their application in flight  engineering. The patterns  of velocity field contour  of  airflow  are  visualized  by  using  numerical  method  in Femlab software. Varying the velocity of airflow, the angle of attack, and the cross section form  of wings shows the visualization of these patterns.  The results of research show that the patterns  of velocity field  contour of airflow around the wings of subsonic plane may be circulation form.  Factors that influence these patterns of contour are the velocity of airflow, the attack angle of wings, and the cross section form  of wings. These three factors  determine lift coefficient and dragcoefficient.  In  commercial flight   it  is  used  airfoil  wings  that  areequipped by rear flaps on the trail edge of wings. These rear flaps canbe lowered of raised to adjust the cross section of airfoil. The slotsetting in the leading edge of wings can reduce the drag coefficient.Accordingly.fuel  efficiency andflight safety can be controlled.